Spatial and ecometric analyses of the Plio‐Pleistocene large mammal communities of the Italian peninsula. (11th April 2013) - Meloro, Carlo; Kovarovic, Kris
Abstract: Aim: Knowledge of mammal community composition across large areas is critical to the reconstruction of biogeographical trends in past ecosystems where mammalian fossils serve as palaeoecological proxies. We employed 'ecometrics' (taxon‐free trait analysis) to compare fossil communities of the Italian Plio‐Pleistocene across space and time. We tested the hypotheses that ecometric traits characterizing fossil mammal communities differ between time bins, and that they exhibit geographical correlations. Location: Peninsular Italy, excluding islands (Sardinia and Sicily). Methods: We explored selected ecometric traits (body weight, biomass, hypsodonty and brachial index) in 69 local fossil assemblages at the scale of nine palaeocommunities (PCOMs), and at the broader scale of 'mammal age', or biochronological unit, to which they belong: Villafranchian, Galerian or Aurelian. Principal components analysis, MANOVA and linear discriminant analysis were used to describe differences in the PCOM and mammal age ecospaces. We also tested for the effects of latitude and longitude on the ecometric variables and mapped their distributions during individual mammal ages. Results: Spatial analysis suggested that neither latitude nor longitude relate meaningfully to any of the ecological parameters under consideration. However, PCOMs in each biochronological interval were successfully discriminated using ecometric traits, with the exception of the localities from Triversa and Pirro, which bore more resemblance to the younger Aurelian localities. The mammal ages were more clearly distinct. Main conclusions: Communities differ from one another particularly in relation to both the average body weight of herbivores and the entire mammalian fauna and the biomass of prey species. This is probably related to a climatic cooling trend that occurred between the Pliocene and Pleistocene and resulted in the evolution of larger forms. Hypsodonty trends are identified and we support hypsodonty as a valuable ecometric trait, but only at larger temporal scales.